Efficacy of smart fertilizer for combating bacterial wilt disease in Solanum Lycopersicum - Radhi, M. Z. A.; Adam, Mohd. Bakri; Mohd Saud, Halimi; Hamid, Mohd Norowi; Peng, Tony Shih Hao; Tan, Geok Hun (Direct Research Journals, 2016)
Tomato plants are susceptible to bacterial wilting, which causes production losses varying from 10 to 100%. In Malaysia, there are more than 35 families of plants are affected by this disease, and the major economic host including potato, tomato, eggplant, chili, ginger and groundnut.Â Although there was no published data on the exact losses in Malaysia caused by Ralstonia solanacearum, however, this disease caused tomato yield losses up to 70 % of farmersâ€™ income.Â This work had the objective of evaluating â€œsmart fertilizerâ€ for controlling and/or preventing bacterial wilt disease and to study the overall growth of tomato plants in control environment. The plants height was increased from week-4 to week-12 with the average of 104.92 cm in treatment T1 (formulated phage fertilizer); 93 cm in treatment T2 (fertilizer alone) and only 43.9 cm in treatment T3 (common commercial fertilizer). The growth performance of tomato plants was dwarfed in T3. There are similar results in stem observation, fresh weight, dry weight and total fruits produced. The total fruits yield in T3 was lesser than one third in both T1 and T2 due to a very high mortality rate in T3 by wilting especially at the fruiting stage of the plantsÂ . Finally, we concluded that the used of smart fertilizer can be used as an alternative for the bacterial wilt control.